Modern Philosophy - Ott, Walter (Open textbook library., 2013)
This is a textbook in modern philosophy. It combines readings from primary sources with two pedagogical tools. Paragraphs in italics introduce figures and texts. Numbered study questions (also in italics) ask students to reconstruct an argument or position from the text, or draw connections among the readings. And I have added an introductory chapter (Chapter 0 – Minilogic and Glossary), designed to present the basic tools of philosophy and sketch some principles and positions. The immediate goal is to encourage students to grapple with the ideas rather than passing their eyes over the texts. This makes for a better classroom experience and permits higher-level discussions. Another goal is to encourage collaboration among instructors, as they revise and post their own versions of the book.